2000
DOI: 10.1097/00005176-200002000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Chronic Hepatitis B in Adolescents or Young Adults in Follow-up From Childhood

Abstract: All children carrying hepatitis B surface antigen should be observed carefully to monitor the possible development of hepatocellular carcinoma, especially in the antihepatitis B e-positive phase after spontaneous seroconversion or even after interferon treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…14 Fujisawa et al followed up 52 children around 11 years of age and they reported seroconversion rate of 50% that was slightly lower than our findings. 15 These findings show that the longer the duration of follow-up, the higher seroconversion to anti-HBe.In this study, we found that seroconversion rate in children born to antiHBeAg-positive mothers (66.1% of 115 cases) was higher than the HBeAg-positive mothers (p < 0.0001). Tseng et al reported that 48.8% children born to 80 HBeAg-positive mothers and 73.7% of 57 children born to anti-HBe-positive mothers seroconverted to anti-HBe.…”
Section: Discussionmentioning
confidence: 85%
“…14 Fujisawa et al followed up 52 children around 11 years of age and they reported seroconversion rate of 50% that was slightly lower than our findings. 15 These findings show that the longer the duration of follow-up, the higher seroconversion to anti-HBe.In this study, we found that seroconversion rate in children born to antiHBeAg-positive mothers (66.1% of 115 cases) was higher than the HBeAg-positive mothers (p < 0.0001). Tseng et al reported that 48.8% children born to 80 HBeAg-positive mothers and 73.7% of 57 children born to anti-HBe-positive mothers seroconverted to anti-HBe.…”
Section: Discussionmentioning
confidence: 85%
“…Three studies [13,19,21] were performed in Europe, three [14,17,20] in Japan, and one each in Thailand [12] and Taiwan [8]. The sample size of each study varied greatly, ranging from 52 [20] to 404 patients [13]. Variable IFN schedules were used, both for total dose and for length of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…During the observation period, 67 children remained untreated, and 41 were treated with IFN-a; these patients had been included in clinical trials performed at our department in previous years [21]. At baseline, treated and untreated patients were comparable with regard to demographic, clinical, and laboratory features (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In a study including 52 children followed up for 3-22 years, Fujisawa et al [21] reported a percentage of HBeAg clearance of 83.3% in untreated patients and 87.5% in treated patients; none of the patients achieved an undetectable HBsAg level. The authors explained that this lower rate of HBsAg clearance was a result of perinatal acquisition of HBV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation